The effectiveness of animated video on social science learning outcomes and activeness in elementary school students - Luhur Wicaksono; Dafid Ginting; Muhammad Rijal Fadli; Jems Sopacua; Iwan Ramadhan; Mega Cantik Putri Aditya (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2023)
Animated video learning media is a tool that can be used in various learning models to improve the quality of learning. However, there are still many social studies teachers who have not utilized animated videos in social studies learning to increase student activity and learning outcomes. The purpose of this research is to analyze the effectiveness of animated videos on the activity and social studies learning outcomes of elementary school students. The method used is a descriptive quantitative approach with an experimental design. The sampling technique used purposive sampling with a sample of 42 students and 1 teacher. Data collection techniques through questionnaires in the form of pre-test and post-test statements with a Likert scale of 5 to assess student activity and learning outcomes. Data analysis used a paired sample t-test to determine whether there was an influence between the two variables assisted by the SPSS Version 26 program. The results showed that the use of animated videos in social studies learning was stated to be effective so that learning activities took place optimally and were able to improve activeness and student learning outcomes.